2023
DOI: 10.1080/13880209.2023.2169468
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of Tripterygium glycosides as an add-on treatment in adults with chronic urticaria: a systematic review and meta-analysis

Abstract: Context Tripterygium glycosides (TG), a traditional Chinese medicine, has been used to treat chronic urticaria (CU) in China, and the evidence of TG for CU needs to be updated thoroughly. Objective To systematically evaluate the efficacy and safety of TG combined with H1-antihistamine (H1-AH) in adults with CU. Methods Eligible randomized controlled trials were searched in eight databases until May 31, 2022, including CNKI, Wan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…It has even been found that long-term use of Tripterygium Glycosides causes skin and mucosal reactions such as oral mucosal ulcers, dryness of the mouth and eyes, roughness and dryness of the skin, rashes, skin sclerosis, and increased melanin production, which is usually associated with the inhibition of the IL-23/IL-17 pathway [51,52]. In addition, long-term use of Tripterygium Glycosides can inhibit ovarian function and cause menstrual disorders such as decreased menstrual flow or amenorrhea in women, and in men, it may lead to a decrease in sperm count or sperm motility [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…It has even been found that long-term use of Tripterygium Glycosides causes skin and mucosal reactions such as oral mucosal ulcers, dryness of the mouth and eyes, roughness and dryness of the skin, rashes, skin sclerosis, and increased melanin production, which is usually associated with the inhibition of the IL-23/IL-17 pathway [51,52]. In addition, long-term use of Tripterygium Glycosides can inhibit ovarian function and cause menstrual disorders such as decreased menstrual flow or amenorrhea in women, and in men, it may lead to a decrease in sperm count or sperm motility [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…Sulfasalazine and Tripterygium Glycosides Tablets are the common immunosuppressive agents which have anti-inflammatory and suppressing effects on cellular and humoral immunity used for treatment in the most case of LCV, 14 , 15 and can quickly resolve both cutaneous and ocular inflammations after treatment. 16 The combination of the 2 drugs is common and effective in the clinic for control of LCV progression.…”
Section: Discussionmentioning
confidence: 99%